2011
DOI: 10.1186/1472-6750-11-90
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of a peptide-based adiponectin receptor agonist for cancer treatment

Abstract: BackgroundAdiponectin, a fat tissue-derived adipokine, exhibits beneficial effects against insulin resistance, cardiovascular disease, inflammatory conditions, and cancer. Circulating adiponectin levels are decreased in obese individuals, and this feature correlates with increased risk of developing several metabolic, immunological and neoplastic diseases. Thus, pharmacological replacement of adiponectin might prove clinically beneficial, especially for the obese patient population. At present, adiponectin-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
150
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(166 citation statements)
references
References 82 publications
(95 reference statements)
5
150
2
Order By: Relevance
“…At present, the results from certain studies support the hypothesis of a protective effect for adiponectin in cancer, through its antiproliferative and apoptosis-inducing activities (49,50). Previous studies have revealed that plasma adiponectin concentrations correlate inversely with BMI (50)(51)(52). However, in the present study, the results did not reveal a significant association between plasma levels of adiponectin and BMI among patients with cancer.…”
Section: Hgf Pg/mlcontrasting
confidence: 99%
“…At present, the results from certain studies support the hypothesis of a protective effect for adiponectin in cancer, through its antiproliferative and apoptosis-inducing activities (49,50). Previous studies have revealed that plasma adiponectin concentrations correlate inversely with BMI (50)(51)(52). However, in the present study, the results did not reveal a significant association between plasma levels of adiponectin and BMI among patients with cancer.…”
Section: Hgf Pg/mlcontrasting
confidence: 99%
“…Hyperadiponectinaemia may be noted as seen in cases with anorexia nervosa 165 . This transient and late increase in APN level has very little influence in the late phase of the pathogenesis of obesity-related cancers, as the disease modifying effects of APN has already altered the course of disease in the early phase.…”
Section: How Important Is Apn In Malignancies?mentioning
confidence: 99%
“…Other agents that may usefully increase adiponectin levels (such a PPARγ agonists, inhibitors of the renin-angiotensin system, calcium channel modulators and some β-receptor antagonists and various natural substances) deserve further study, although at present data are limited and have not been applied to oesophageal disease [Lim et al 2014]. Adiponectin analogues [Otvos et al 2011] and leptin receptor antagonists [Rene Gonzalez et al 2009] are in preclinical development but these appear some way off clinical use.…”
Section: Implications For Therapymentioning
confidence: 99%